PERANCANGAN SISTEM INFORMASI MONITORING KINERJA SALES BERBASIS WEB MENGGUNAKAN KONSEP GAMIFICATION (Studi Kasus Sales Team Unit BGES PT Telkom Bekasi) - Lulu Zaujatun Sholekhah (2022)
Technological developments develop hand in hand in solving problems in various aspects of life. The use of technology in monitoring sales of the Telkom Bekasi BGES Unit which is engaged in marketing has not yet implemented an automated system so that there are delays in the interaction process and sending data or information through the Telegram and Google Sheet applications. By using this sales performance monitoring information system, activities in monitoring sales performance will be maximized in making it easier for users to access real time data and information. The design of this sales performance monitoring system uses the concept of gamification or game pattern design using point and leaderboard elements that will increase user interest in creating a structured work ethic. The information system design method in this study uses the PIECES method in system analysis, and the Waterfall method in system development, then the system implementation uses the CodeIgniter 4 Framework, and uses system modeling with Unified Modeling Language (UML). The results of this study are the creation of a sales performance monitoring information system with the latest sales performance appraisal features in the form of leaderboard rankings, customer data management, customer order status management, and sales force data management. With the hope of increasing the productivity of the sales performance to achieve the company's sales targets.